Ora, Direis Ouvir Estrelas: Historiografia e História do Teatro Brasileiro - Brandão, Tania (Latin American Theatre Review, 2002)
This study emphasizes that Brazilian theatre history has been written following a pattern inherited from the 19th century. This statement implies that the most important works in this area were conceived according to historical concepts that are inadequate for analyzing modern theatre or even for working with contemporary theatre, because the 20th century represents a decline in aspects of mise-en-scène, performance and mimesis. One might ask if the authors considered are not dealing with a conception of history absolutely foreign to this cultural field. I propose that history has to be rethought in order to achieve another kind of theatre history, different from the old model seen in traditional books. (TB, in Portuguese)